2010
DOI: 10.1002/jat.1518
|View full text |Cite
|
Sign up to set email alerts
|

Methamidophos, dichlorvos, O‐methoate and diazinon pesticides used in Turkey make a covalent bond with butyrylcholinesterase detected by mass spectrometry

Abstract: Organophosphorus pesticides used most commonly in Turkey include methamidophos, dichlorvos, O-methoate, and diazinon. These toxic chemicals or their metabolites make a covalent bond with the active site serine of butyrylcholinesterase. Our goal was to identify the adducts that result from the reaction of human butyrylcholinesterase with these pesticides. Highly purified human butyrylcholinesterase was treated with a 20-fold molar excess of pesticide. The protein was denatured by boiling and digested with tryps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The average BChE nonapeptide concentration in human serum was found to be 40.0 ± 9.8 ng/mL with a range of 18.4-61.7 ng/mL, which was in agreement with results previously reported . A BChE nonapeptide concentration of 40.0 ng/mL in serum is representative of a BChE enzyme concentration of 50 nM which is consistent with previously reported concentrations of BChE in human serum (Lockridge, 2015;Noort, Benschop, & Black, 2002;Tacal and Lockridge, 2010 (Berry and Davies, 1966).…”
Section: Matrix Blank Serum and Convenience Set Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The average BChE nonapeptide concentration in human serum was found to be 40.0 ± 9.8 ng/mL with a range of 18.4-61.7 ng/mL, which was in agreement with results previously reported . A BChE nonapeptide concentration of 40.0 ng/mL in serum is representative of a BChE enzyme concentration of 50 nM which is consistent with previously reported concentrations of BChE in human serum (Lockridge, 2015;Noort, Benschop, & Black, 2002;Tacal and Lockridge, 2010 (Berry and Davies, 1966).…”
Section: Matrix Blank Serum and Convenience Set Analysissupporting
confidence: 90%
“…(Pantazides et al, 2014) A BChE nonapeptide concentration of 40.0 ng/mL in serum is representative of a BChE enzyme concentration of 50 nM which is consistent with previously reported concentrations of BChE in human serum. (Lockridge, 2015, Noort et al, 2002, Tacal and Lockridge, 2010) Only the unadducted BChE biomarker was found to be present in the convenience set; no aged OPNA-BChE adducts were detected.…”
Section: Resultsmentioning
confidence: 95%
“…We reported that single doses of diazinon (commercial‐grade) phosphorylated nuclear sperm protamines at serine residues altering sperm chromatin structure in mice (Piña‐Guzmán et al,). Similarly, MET (technical‐grade) efficiently inhibited purified butyrylcholinesterase forming adducts with the enzyme by the addition of methoxy aminophosphate (Tacal and Lockridge,). Studies are in progress to evaluate METt phosphorylating ability in sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…), including serine, tyrosine, lysine and histidine in various proteins. Organophosphorylation at amino acid residues is dose‐ and site‐dependent, and most identified modifications occurred at tyrosine and lysine residues on protein surface regions in the vicinity of positively charged amino acids …”
Section: Ms‐identified Protein Adductsmentioning
confidence: 99%
“…Organophosphorylation at amino acid residues is dose-and site-dependent, and most identified modifications occurred at tyrosine and lysine residues on protein surface regions in the vicinity of positively charged amino acids. [24,25,28] Each OP molecule makes a particular added mass when adducted to an amino acid residue (see Table 1) and can be identified by MS, mostly via bottom-up approaches. Using MS, multiple covalent modifications have been identified in various proteins, and MS/MS has determined the modification sites for albumin, tubulin, actin, keratin, transferrin, ubiquitin, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), mostly at tyrosine, lysine and serine residues.…”
Section: Organophosphate Adducts and Toxicitymentioning
confidence: 99%